Foam rolling and joint distraction with elastic band training performed for 5-7 weeks respectively improve lower limb flexibility - Guillot, A.; Kerautret, Y.; Queyrel, F.; Schobb, W.; Di Rienzo, F. (Journal of Sports Science & Medicine, 2019)
Both foam rolling and joint distraction training with elastic bands are very popular interventions designed to improve muscular function, motor performance, and joint range of motion, as well as to reduce feeling of fatigue and delayed onset of muscle soreness. The heterogeneity of methods used among studies however prevents from drawing firm conclusions about the optimal content of pre/post interventions. The present study aims at answering the following questions: i) Do foam rolling and joint distraction with elastic band training improve joint range of motion in national rugby players? ii) Do short and long rolling durations have similar effects on range of motion? In a first experiment, we compared ankle, knee, and hip flexibility scores in 30 national rugby players after a 7-week foam rolling training program involving either a short (20s) or long (40s) rolling duration. Data revealed that foam rolling substantially improved all range of motion scores, regardless the rolling duration (performance gains ranged from 9 to 18° in the foam rolling groups, i.e. 8 to 20% increase, but remained under 2° in the control group). In a second experiment, we investigated the effect of a 5-week joint distraction with elastic band training program on hamstring and adductor range of motion in 23 national rugby players. Data showed that elastic band training significantly improved sit-and-reach (29.16% increase, p = 0.01) as well as side split (2.31% increase, p < 0.001) stretching performances. Taken together, present findings confirm that both foam rolling and joint distraction exercises with elastic bands are likely to enhance joint range of motion and specific mobility patterns during sport performance, and further serve prophylaxis. Such effects therefore constitute a promising avenue for clinical, home therapy, and personal flexibility training